Challenges and Opportunities for Human Resource Management in the Industrial Era 4.0: Focus on the Integration of Technology and Human Resources - Agus Anggiana; Ahmad Gunawan (Jurnal Ekonomi dan Bisnis Digital, 2022)
The Industry 4.0 era has brought profound changes in the way businesses and organizations operate. The development of information and communication technology has enabled the application of advanced technologies, such as artificial intelligence, the internet of things, and automation which have fundamentally changed the business landscape. In this context, human resource management (HR) faces new, unprecedented challenges and opportunities. In the Industry 4.0 era, HR not only has to manage the human workforce but also has to integrate increasingly sophisticated technology. This requires a thorough understanding of the technology used as well as the ability to select, implement and manage relevant technology solutions. On the other hand, the Industry 4.0 era also opens up great opportunities to increase the efficiency and productivity of human resource management. This research emphasizes the importance of progressive and innovative human resource management to face the challenges and take advantage of the opportunities brought by the Industry 4.0 era. Through a combination of technology and human intelligence, organizations can gain a competitive advantage and create a dynamic and responsive workplace in the digital era.